Predicting the development of acute kidney injury in liver cirrhosis – an analysis of glomerular filtration rate, proteinuria and kidney injury biomarkers. Issue 10 (12th April 2013) - Slack, A. J.; McPhail, M. J. W.; Ostermann, M.; Bruce, M.; Sherwood, R.; Musto, R.; Dew, T.; Auzinger, G.; Bernal, W.; O'Grady, J.; Heneghan, M. A.; Moore, K.; et al.
Summary: Background: The timely diagnosis of acute kidney injury (AKI) in liver cirrhosis is challenging. Aim: To evaluate whether quantification of glomerular filtration rate (GFR), proteinuria and kidney injury biomarkers can accurately predict the development of AKI. Methods: A prospective cohort analysis of patients with cirrhosis was performed. Measures of baseline kidney function included serum creatinine, iohexol clearance and urine protein:creatinine ratio. Blood and urine samples were collected daily. A retrospective analysis of cystatin C GFR and neutrophil gelatinase‐associated lipocalin (NGAL) measured 48 h prior to the diagnosis of AKI was undertaken to evaluate their ability to predict the development of AKI. Results: Eighteen of the 34 cirrhosis patients studied developed AKI. A GFR <60 mL/min/1.73 m 2 was identified in 56% with Iohexol clearance compared to 8% using the four‐variable modified diet in renal disease formula ( P < 0.0001). Prediction of AKI, 48 h prior to the development of AKI with cystatin C GFR and serum NGAL concentration were similar; area under the receiver operating curve (AUROC) values 0.74 (0.51–0.97), P = 0.04 and 0.72 (0.52–0.92), P = 0.02 respectively. The development of AKI was strongly predicted by urine protein:creatinine ratio above the cut‐off of >30 (equivalent to 300 mg/day of proteinuria) sensitivity 82% (57–96) and specificity 80% (52–96), AUROC 0.86 (0.73–0.98), P ≤ 0.0001. [OR 21 (3–133), P ≤ 0.002]. Conclusions: In patients with liver cirrhosis a urine protein:creatinine ratio >30 predicts AKI. Iohexol clearance and cystatin C formulae identify a greater proportion of patients with a GFR <60 mL/min/1.73 m 2, which also predicts the development of AKI.